JS09.6.A Low incidence of radiation-induced brain lesions and stable QoL following proton irradiation for CNS and Skull Base tumors- results from the prospective MedAustron register REGI-MA-002015. (5th September 2022) - Lütgendorf-Caucig, C; Flechl, B; Konrath, L; Pelak, M; Fraller, A; Mock, U; Fossati, P; Stock, M; Georg, P; Hug, E
Abstract: Background: Irradiation of intracranial tumors may induce endothelial damage in the surrounding normal brain tissues, resulting in an increase of capillary permeability. These changes can be depicted on magnetic resonance imaging (MRI) as a new contrast medium uptake - not associated with tumor. Radiation-induced brain lesions (RIBL) occur after photon as well as proton irradiation. This study evaluated the incidence of RIBL after proton irradiation and their impact on Quality of Life (QoL). Material and Methods: 421 patients treated between 01/2017 and 06/2021 were included. All patients participated in a prospective registry study (ClinicalTrials.gov Identifier: NCT03049072). Follow-up evaluations including MRIs were at 3, 6, 12 months after treatment completion and annually thereafter. QoL parameters were assessed by EORTC-CTC30 and BN20 questionnaires. Results: 48.9% (n=206) patients received therapy for intracranial non-CNS tumors (meningioma, pituitary adenoma, and other), 26.8% (n=113) for head and neck cancer with skull base involvement, 14.5% (n=61) for primary CNS tumors and 9.7% (n=41) for skull base tumor. Median follow-up was 24 months (range 6-54 ), 352 (86%) patients had proton therapy as primary treatment, 59 (14%) had salvage treatment with proton re-irradiation (ReRT). Median prescribed dose was 58.5 Gy (RBE) (range 40-78 Gy (RBE)), median D1% of brain tissue was 54.3 Gy (RBE) (range 30-76 Gy RBE). Local control and overall survival were 91% and 95% at 2 years. The cumulative RIBL incidence was 15.0% (n=63), with significantly lower occurrence in the primary RT group vs. the ReRT group (12.9% vs. 27.1%; p<0.001). According to Grade, the distribution was 10.5% (n=44) Grade I (asymptomatic, MRT finding only), Grade II RIBL, 13 (3.1%) (moderate symptoms) (grade 2) and 1, 4% (n=6) developed Grade 3 toxicity. Actuarial 2-year RIBL incidence was 18.2% (95%CI: 14.1-23.2) for the all Grades and the entire, 15.7% (95%CI: 11.6-21) following primary radiation and 34.2% (95%CI: 21.9-50.9) after ReRT. All RIBL developed outside the residual tumor, but inside the Planning Target Volume (PTV), median D1% was 60.3Gy (RBE) (range 46.1- 122.3 Gy(RBE)), median time to development was 11.8 months (range 2.7-37 months) in the total cohort, for primary RT 14.2mo (4.3mo -37.1mo) and 6.0mo (2.7mo -19.3mo) following ReRT. At the time of analysis 26 of the 63 RIBL had resolved (41.3%). General QoL was not compromised. In a matched-pair analysis of 54/50 patients with/without RIBL, only at the 12 month a significant difference in the global health score in favour of non-RIBL patients was observed. At 24 months the score for RIBL patients improved without difference between the groups. Conclusion: Overall incidence of RIBL after proton radiotherapy is very low - even for skull base tumors requiring high total doses and it had no significant negative impact on long term QoL.